Campaña de posicionamiento, en la categoría de hoteles boutique. Caso: Selina - García Ayala, Cristina Nicole (2019)
The following degree work presents an alternative advertising campaign that is focused on young people, as it is the target group to which Selina is directed. The reason for this study arises from the growing trend that has taken place in ecent years worldwide that are boutique hotels. For this reason, it is importantto carry out a study that helps to add to the new trend of these hotels since,being relatively new in Ecuador, it is a source of economic and cultural growth.The purpose of this is to determine what the local and nomadic tourist is lookingfor at the moment of traveling and contemplate activities within the city. Through the help of several research tools it was possible to identify the behavior of the consumer, determining what they are looking for today and understand their lifestyle. It is essential to understand that the activities they carry out within the city are done with their friends, they decide to share the moments through their networks. Which indicates that today young people want to express what they do. Without being afraid to shut up what they think. Millennials are looking for different activities all the time, however, until now it has not been possible to determine which places can go to perform different activities within Quito. One of the most relevant findings that can be obtained thanks to the research is that young people are open to listen to fun options and want to know different cultures. With these findings we have been able to develop several tactics that would encourage this target group to learn about this different concept that Selina manages in Ecuador, as an option for travel and recreational activities within the capital.